2021
DOI: 10.1088/2631-7990/ac3bb1
|View full text |Cite
|
Sign up to set email alerts
|

Wideband mid-infrared thermal emitter based on stacked nanocavity metasurfaces

Abstract: Efficient thermal radiation in the mid-infrared (M-IR) region is of supreme importance for many applications including thermal imaging and sensing, thermal infrared light sources, infrared spectroscopy, emissivity coatings, and camouflage. The capability of controlling light makes metasurface an attractive platform for infrared applications. Recently, different metamaterials have been proposed to achieve high thermal radiation. To date, broadening of the radiation bandwidth of metasurface emitter (meta-emitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The current advanced stacking and packaging technologies [213][214][215][216][217][218] offer access to integrating the lens wafer on the photosensor wafer. Hu et al 215 demonstrated fullcolor holography by stacking a metasurface upon a layer of color filter array (Fig.…”
Section: Wafer Stacking and Packagingmentioning
confidence: 99%
“…The current advanced stacking and packaging technologies [213][214][215][216][217][218] offer access to integrating the lens wafer on the photosensor wafer. Hu et al 215 demonstrated fullcolor holography by stacking a metasurface upon a layer of color filter array (Fig.…”
Section: Wafer Stacking and Packagingmentioning
confidence: 99%
“…Landy first introduced the metamaterial perfect absorber (MPA) [ 11 ], which has opened a new research area due to its extensive use in different applications such as energy harvesting [ 12 ], solar cells [ 13 ], photodetectors [ 14 ], and thermal emitters. [ 15 ]. Researchers are currently conducting extensive research on the MPA design for application in the infrared, THz, and microwave frequencies, and they are achieving low-loss devices through structural optimization [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since it may be used in a variety of applications, such as absorber [ 3 ], polarization converter [ 4 ], filter [ 5 ], imaging [ 6 ], antenna [ 7 ], invisible clock [ 8 ], sensor [ 9 ], waveguides [ 10 ], etc. The perfect metamaterial absorber was first developed by Landy [ 11 ], which started an innovative study area for its unique use in many applications, such as photo-detecting [ 12 ], energy harvesting [ 13 ], thermal emitter [ 14 ], and solar cell [ 15 ], etc. Researchers are now pursuing research on the metamaterial perfect absorber design for microwave frequency, visible, infrared, and THz applications and developing low-loss devices by structural optimization [ 16 ].…”
Section: Introductionmentioning
confidence: 99%